Endothelial Cells in Antibody-Mediated Rejection of Kidney Transplantation: Pathogenesis Mechanisms and Therapeutic Implications - Shuo Wang; Chao Zhang; Jina Wang; Cheng Yang; Ming Xu; Ruiming Rong; Tongyu Zhu; Dong Zhu (Journal of Immunology Research)
Antibody-mediated rejection (AMR) has been identified as a main obstacle for stable immune tolerance and long survival of kidney allografts. In spite of new insights into the underlying mechanisms of AMR, accurate diagnosis and efficient treatment are still challenges in clinical practice. Endothelium is the first barrier between recipients’ immune systems and grafts in vascularized organ transplants. Considering that endothelial cells express a number of antigens that can be attacked by various allo- and autoantibodies, endothelial cells act as main targets for the recipients’ humoral immune responses. Importantly, emerging evidence has shown that endothelial cells in transplants could also initiate protective mechanisms in response to immune injuries. A better understanding of the role of endothelial cells during the pathogenesis of AMR might provide novel therapeutic targets. In the present review, we summarize the antigens expressed by endothelial cells and also discuss the activation and accommodation of endothelial cells as well as their clinical implications. Collectively, the progress discussed in this review indicates endothelial cells as promising targets to improve current diagnosis and therapeutic regimens for AMR.